Hybrid process for the purification of water contaminated with nitrites: Ion exchange plus catalytic reduction - Mendow, Gustavo (2017)
Water polluted with nitrites represents a big risk to human health. In this work, palladium supported on macroporous anionic exchange resin was used in the catalytic nitrite reduction. This process is compared with the traditional ion exchange procedure using the same catalytic resin. Both, the resin and the catalyst behaviour were evaluated in a fix-bed reactor, feeding water containing nitrites and other competitor ions, such as sulphate, bicarbonate, and chlorides, and adjusting the pH with carbon dioxide. When feeding water containing only nitrites, it was observed that the catalytic reduction makes it possible to treat 55% more water than when using the ion exchange process, at the same level of nitrites elimination. Moreover, in steady state it was possible to obtain a nitrite conversion to nitrogen of 54% with high selectivity, obtaining an ammonium concentration lower than 0.2 mg/L. In the case of having other ions present in the system, both the conversion and the selectivity decreased. A regeneration strategy is also developed, using a very low hydrogen flow rate at atmospheric pressure and room temperature. This treatment leads to the reduction of more than 99% of the nitrites present in the contaminated water. The catalyst was used in several consecutive cycles maintaining a very good performance, even in the presence of competitor ions. The process was scaled up to a pilot level obtaining identical results.